Fekete-Szegö Problem for α-Quasi Convex Functions of Order β - Selvaraj, C.; Geetha, R. (Journal of Informatics and Mathematical Sciences, 2012)
For f Q_α,β^c, sharp bounds are obtained for the Fekete-Szegö functional |a_3 - μ a_2^2|, where μ is real.